Clinical Application of Platelet-Rich Fibrin in Dermatology - Qing-Yun Wu; Qian Zhang; Fang Fang; Wen-Bo Bu (International Journal of Dermatology and Venerology, 2022)
Platelet-rich fibrin (PRF) is a second-generation platelet concentrate obtained from autologous blood. PRF is composed of abundant platelets, leucocytes, and a high concentration of various growth factors and fibrinogen. The composition and three-dimensional structure of PRF enable it to effectively make cells migrate and proliferate, playing an important role in tissue repair. Furthermore, the easy preparation and low cost of PRF make it a good treatment option. Numerous articles have been published about the application of PRF in clinical practice, however, the application of PRF in dermatology has not been comprehensively reviewed. The objective of this review article was to discuss various applications of PRF in dermatology, including healing chronic wounds, treating androgenic alopecia, skin rejuvenation, autologous fat transplantation, and treating vitiligo. PRF is a promising dermatologic treatment, but lacks a standardized protocol regarding its methods of attainment and use, which needs more investigations.